(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article deals with the peculiarities of implementing 21st century skills into language classroom. It encourages students to think outside the box and think about ways to give directions using a computer, a mobile phone, a television, or a YouTube video. While there may be some L1 use in the classroom, the goal is for the final product to be in English.